Marketplace Atmosphere Sebagai Stimulus Gaya Belanja Hedonis dan Utilitarian Terhadap Kepuasan Belanja Online - Isalman (Politeknik Negeri Bali, 2025)
The attractive atmosphere of the marketplace can be a fundamental element that can influence the shopping experience on the marketplace platform. In addition to fostering a hedonic shopping style, marketplace atmosphere can also strengthen utilitarian shopping styles. Therefore, this study aims to determine the impact of marketplace atmosphere on hedonic shopping styles, utilitarian shopping styles, and online shopping satisfaction. The study was conducted on Shopee marketplace users in Kendari City. The sample size was 150 respondents. Data were collected through purposive sampling using a questionnaire and analyzed using SmartPLS Structure Equation Modeling (SEM). The results of the data analysis indicate that directly and indirectly, marketplace atmosphere has a significant positive effect on hedonic shopping styles, utilitarian shopping styles, and online shopping satisfaction. Furthermore, hedonic shopping styles and utilitarian shopping styles have a significant positive effect on online shopping satisfaction. These findings have provided marketplaces with an overview of the urgency of arranging the visualization of various display elements, features, and navigation that create a market atmosphere, arouse hedonic motivation, and strengthen utilitarian shopping styles to achieve online shopping satisfaction.